Tromboembolismo pulmonar séptico de origen genital: Histerectomía y ligadura secundaria de la vena cava inferior - Armand Ugon, César; Alvarez, julio; Otazú, Heber; Martínez, José Luis; Ituño, Carlos (Cirugía del Uruguay, 1980)
The authors report a case of thromboembolism septic lung, of female genital origin, - that had a good evolution, only when, or was added, secondary to hysterectomy, the interruption of the inferior vena cava.